PERANCANGAN MEDIA IKLAN PROMOSI UMKM PESONA CEMILAN RINGAN - Ayyub Hamdanu Budi Nurmana MS; Rozalia Stevany (LPPM Politeknik Pratama Kendal, 2025)
Promotional activities are carried out by companies to inform and give consumers confidence about the product. Promotional media, such as brochures, are used to introduce products or services to the public. An attractive brochure design will make it easier for the product to be known and reach various groups. Brochures contain information about the company, products, services, or recent changes. A clear and attractive brochure design is expected to attract the attention of new customers and increase public interest in buying. Therefore, designing advertising media for UMKM Pesona Semilan Ringan Semarang is important.